Crossover from positive to negative optical torque in mesoscale optical matter. Issue 1 (December 2018) - Han, Fei; Parker, John; Yifat, Yuval; Peterson, Curtis; Gray, Stephen; Scherer, Norbert; Yan, Zijie
Abstract The photons in circularly polarized light can transfer their quantized spin angular momentum to micro- and nanostructures via absorption and scattering. This normally exerts positive torque on the objects wher the sign (i.e., handedness or angular direction) follows that of the spin angular momentum. Here we show that the sign of the optical torque can be negative in mesoscopic optical matter arrays of metal nanoparticles (NPs) assembled in circularly polarized optical traps. Crossover from positive to negative optical torque, which occurs for arrays with different number, separation and configuration of the constituent particles, is shown to result from many-body interactions as clarified by electrodynamics simulations. Our results establish that both positive and negative optical torque can be readily realized and controlled in optical matter arrays. This property and reconfigurability of the arrays makes possible programmable materials for optomechanical, microrheological and biological applications. Negative optical torque has been predicted theoretically, but experimental demonstrations have been scarce. Here, the authors show that the optical torque in a mesoscopic optical matter array can be reversed depending on number, separation and configuration of nanoparticles in a circularly polarized optical trap.